Reconhecimento, justiça e reificação em Axel Honneth - Silva, José Claudio de Sousa da (2023)
This paper aims to examine the relevance and necessity of the relationship between the concepts of Recognition, Justice and Reification present in the reflections of the philosopher Axel Honneth (1949-) in the current debates. The research is based on the works Fight for recognition (2009), Redistribution or recognition? (2003) and Reification (2018). In Struggle for recognition, it was found that Honneth dedicated himself in the construction of the positive aspects (love, law and solidarity) and the process of practical self-report (self-confidence, self- respect and self-esteem). However, the feeling that represented a greater importance for the subject in his search for recognition was disrespect, non-recognition. It is through this frustration of expectations that a moral experience arises that expresses itself in the feeling of disrespect. It is from disrespect that emerges the necessary impulse for a social conflict, for a struggle for recognition. When do we approach Redistribution or recognition? show that the philosopher Nancy Fraser (1947-) has as a principle the denial that the concept of redistribution is derived from the concept of recognition. Thus, it was observed that the philosopher proposed a dualistic analysis by considering both categories (claims for redistribution and claims for recognition) as irreducible dimensions of justice without reducing them to each other. In the case of Honneth, struggles for material redistribution and struggles for recognition are included in his theory of recognition, to the extent that the sense of injustice that provides them has its origin in violations of expectation of recognition. Thus, Honneth’s theory escapes Fraser’s criticism by re-updating the concept of recognition based on the sense of disrespect that instigates the struggles for redistributive demands and demands for cultural recognition. When dealing with the work Reification (2018), it was found that Honneth proposes a re-updating of the concept of reification, questioning whether the Lukatian concept currently has a diagnostic potential for social pathologies present in societies. For Honneth, reification involves a habit or custom that is externalized through the mere observer behavior of a subject whose perspective of the natural surrounding world, of the world of social relations and of their own personal capacities constitutive of their personality are apprehended with indifference and in a neutral way in relation to affections as if they possessed the qualities of a "thing". For him, at the heart of all reification is present the representation of a process of forgetfulness of recognition.